A Genealogy of Autonomy: Freedom, Paternalism, and the Future of the Doctor–Patient Relationship. Issue 3 (5th May 2021) - Genuis, Quentin I T
Abstract: Although the principle of respect for personal autonomy has been the subject of debate for almost 40 years, the conversation has often suffered from lack of clarity regarding the philosophical traditions underlying this principle. In this article, I trace a genealogy of autonomy, first contrasting Kant's autonomy as moral obligation and Mill's teleological political liberty. I then show development from Mill's concept to Beauchamp and Childress' principle and to Julian Savulescu's non-teleological autonomy sketch. I argue that, although the reach for a new principle to guide choices in physician–patient relationships can rightfully be seen as important, the notion that is now called autonomy within bioethics has corollaries that undermine critical aspects of medical care. As such, there is need for a richer account of the interplay between the free choice of patients and the informed recommendations of doctors.